2013
DOI: 10.1123/jpah.10.4.461
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Comparison of Perceived Benefits and Barriers to Exercise Between Obese and Nonobese Women

Abstract: Background Obese women have lower levels of physical activity than non-obese women, but it is unclear what drives these differences. Methods Mixed methods were used to understand why obese women have lower physical activity levels. Findings from focus groups with obese white women age 50 and older (N=19) were used to develop psychosocial items for an online survey of white women (N=195). After examining the relationship between weight group (obese vs. non-obese) and exercise attitudes, associated items (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 20 publications
4
62
1
2
Order By: Relevance
“…CBOs = community-based organizations; PAI = Perceived Accomplishment Index; AAI = actual accomplishment index. (Creswell, 2003;Leone & Ward, 2013). This agreed with the works of Reinikka and Collier (2001), Collier and Hoeffler (2002), Collier (2003), Short (2003), Narman and Vidanapathirana (2005), and Luckham (2017).…”
Section: The Balance Between Pai and Aai Of Sociophysical Projects Emsupporting
confidence: 77%
“…CBOs = community-based organizations; PAI = Perceived Accomplishment Index; AAI = actual accomplishment index. (Creswell, 2003;Leone & Ward, 2013). This agreed with the works of Reinikka and Collier (2001), Collier and Hoeffler (2002), Collier (2003), Short (2003), Narman and Vidanapathirana (2005), and Luckham (2017).…”
Section: The Balance Between Pai and Aai Of Sociophysical Projects Emsupporting
confidence: 77%
“…Qualitative studies by Peacock et al (2014) and Thomas et al (2008) report health issues in general as barriers to physical activity; however, methodological and reporting limitations make it difficult to interpret exactly what is meant by these findings. Several women surveyed by Leone and Ward (2013) for the quantitative part of their mixed methods study mentioned that illness or medical conditions prevented them from taking part in physical activity; however, again this was not elaborated on. Bond et al (2013) and Napolitano et al (2011) both identified lack of energy as a barrier in obese individuals, but prevalence is not significantly different from the general population (Napolitano et al, 2011).…”
Section: Physical Barriersmentioning
confidence: 91%
“…Also, a qualitative study that explored PA experiences of bariatric surgery candidates found that excess weight was considered an obstacle to PA, primarily due to joint pain and difficulty due to a bigger body size, in addition to self-consciousness [29]. In studies that compared obese adults to their non-obese counterparts, physical barriers such as pain and tiredness and feeling self-conscious were more frequently reported by obese people [19,25,30]. Thus, converging evidence from multiple studies that involved varied designs suggests that physical and self-presentational barriers are particularly important for obese people.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous research has investigated barriers and facilitators to PA in overweight and obese adults [24,25], there is a relative dearth of research on bariatric surgery candidates [26]. Bariatric surgery candidates may have a different perception of factors that influence PA when compared to the general obese population, since surgery is usually considered after repeated unsuccessful attempts to lose weight using conservative methods [27].…”
Section: Introductionmentioning
confidence: 99%